Project-based learning and junior high school students’ learning independence in biology: A pretest–posttest study - Dian Ristiani Sabat; Nonci Melinda Uki; Dewi Fatmawati (JPBI (Jurnal Pendidikan Biologi Indonesia), 2026)
Background: Learning independence is essential for students who must plan, monitor, and evaluate their learning, yet evidence from resource-constrained secondary-school settings remains limited. Objectives: This study examined changes in the learning independence of 29 eighth-grade students after project-based learning (PjBL) was implemented in biology at SMP Negeri 3 Soe, Indonesia. Methods: A one-group pretest–posttest design was used because the available dataset contained complete paired observations only for the class receiving PjBL. Learning independence was measured using a questionnaire administered before and after the intervention. Descriptive statistics, the Wilcoxon signed-rank test, and a paired-samples t-test as a sensitivity analysis were used. Results: The mean score increased from 37.79 (SD = 1.76) to 46.41 (SD = 3.47), representing an 8.62-point improvement. The reported paired-samples test was significant, t(28) = 14.16, p < .001, with a very large standardized mean change (Cohen’s dz = 2.63). The nonparametric analysis also indicated a significant pretest–posttest difference (p < .05). These findings suggest that PjBL may support learning independence by requiring students to plan tasks, manage time and resources, make decisions, monitor progress, and reflect on project outcomes. However, the absence of an analyzable control group limits causal inference. Conclusion: Future research should use controlled designs, report instrument validity and reliability in detail, and examine which PjBL components most strongly support students’ self-regulation.